PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP MINAT KUNJUNGAN ULANG PADA TOKO RIMA DI SANGATTA - Alfian Alfian; Amransyah Amransyah; Nurlianti Nurlianti (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2022)
This study aims to determine 1) the effect of service quality on the interest of, 2) the influence of customer satisfaction on the interest of repeat visits, 3) the quality of service and customer satisfaction simultaneously affect the interest of repeat visits. The population in this study were customers at Toko Rima with a sample of 100 people. The sampling technique in this study used purposive sampling. The data analysis technique used in this research is the IBM SPSS Statistics 25 application. From the results of the analysis using regression, it can be seen that the variables of service quality, and customer satisfaction have a positive effect on interest in repeat visits at Rima Stores with service quality being the variable that has the most influence on interest in repeat visits, followed by customer satisfaction having an effect on interest in repeat customer visits.